Vitamin C and Vitamin D3 show strong binding with the amyloidogenic region of G555F mutant of Fibrinogen A alpha-chain associated with renal amyloidosis: proposed possible therapeutic intervention - Pande M.; Kundu D.; Srivastava R. (My University, 2025)
G555F mutant of Fibrinogen A alpha-chain (FGA) is reported to be associated with kidney amyloidosis. In the current study, we have modelled the G555F mutant and examined the mutation’s effect on the structural and functional level. We have also docked Vitamin C and D3 on the mutant’s amyloidogenic region to identify if these vitamins can bind amyloidogenic regions. Further, we analyzed if they could prevent or modulate amyloid formation by stopping critical interactions in amyloidogenic regions in FGA. We used the wild type FGA model protein as a control. Our docking and molecular dynamics simulation results indicate stronger Vitamin D3 binding than Vitamin C to the amyloidogenic region of the mutant protein. The RMSD, radius of gyration, and RMSF values were higher for the G555F mutant than the FGA wild type protein. Overall, the results support these vitamins’ potential as a therapeutic and anti-amyloidogenic agent for FGA renal amyloidosis. Graphic abstract: [Figure not available: see fulltext.]. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.